Pengembangan Sistem E-Commerce Penjualan Rumah Dengan Pemanfaatan Teknologi Virtual Reality Di Kota Palembang - Pacu Putra; Jaidan Jauhari; Paulus Paskah Lino Susilo; Allsela Meiriza (Jurnal Sistem Informasi, 2018)
ABSTRACTIn the present day, business of properties especially in house selling, is getting thrive day by day. The growth of the business also walks in the same way with the promotional media. But in reality, we often find that either the owner of the house or the prospective buyers, they have the same problem for the promotional media that is too mediocre. In response to the problem, the writer is trying to develop an e-commerce information system using ‘Development of E-Commerce System for House Selling Using C2C Model with Virtual Reality Technology in Palembang’ as the title, in order to solve the problem. The main purpose of this research is to create and develop an e-commerce system for property business especially in housing business at Palembang city. The other purpose of the research is also to implement the technology of virtual reality in e-commerce system. In this case, the virtual reality will help the prospective buyers to have a look at the condition of the house, outside and inside, virtually. So the prospective buyers do not have to physically come to the house. The method for the development of the system that used by the writer is waterfall method. From the system that has already been developed, there are several features that users can use, such as promoting the house online with virtual reality support, and many more. The writer uses the virtual reality with the hope that, this can be a fresh movement in the world of property business especially in the promotional media for house selling. In the process of development, the writer used PHP as the language of the program and MySQL as the database.Keyword : Property Business, House Selling, Waterfall, E-Commerce, Virtual Reality.ABSTRAKBisnis properti di kota Palembang khususnya penjualan rumah, semakin berkembang dari tahun ke tahun dengan berbagai macam media penjualan. Namun dalam penerapannya, tidak jarang ada keluhan yang didapatkan dari pemilik rumah maupun pelanggan, salah satunya mengenai media promosi yang itu-itu saja. Menanggapi keluhan itu, penulis merancang sebuah sistem informasi e-commerce, dengan mengangkat judul “Pengembangan Sistem E-Commerce Penjualan Rumah Menggunakan Model C2C Dengan Pemanfaatan Teknologi Virtual Reality Di Kota Palembang” yang diharapkan mampu membantu mengatasi keluhan yang ada. Tujuan dari penelitian ini yakni membuat perancangan sistem e-commerce untuk bisnis penjualan rumah khususnya yang berada di kota Palembang. Tujuan lain dari penelitian ini juga untuk mengimplementasikan teknologi virtual reality pada sistem e-commerce penjualan rumah, yang akan menampilkan dan memperlihatkan kondisi dari rumah yang dijual, sehingga pembeli tidak perlu datang langsung untuk melihat situasi dari rumah tersebut. Metode yang diimplementasikan dalam sistem ini adalah metode waterfall. Dari sistem yang telah dirancang, dapat memberikan fasilitas berupa pemasangan iklan secara online dengan dukungan realitas maya, yang diharapan mampu menjadi sarana pemasaran baru bagi bisnis properti, khususnya penjualan rumah. Perancangan yang dilakukan, menggunakan bahasa pemrograman PHP dan database MySQL.Kata kunci : Bisnis Properti, Penjualan Rumah, Waterfall, E-Commerce, Virtual Reality